2019
DOI: 10.1038/s41433-019-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the surgical outcome of 27-gauge pars plana vitrectomy for primary rhegmatogenous retinal detachment between air and SF6 gas tamponade

Abstract: relevant financial relationships. M.N. has disclosed the following relevant financial relationships: received grants for clinical research from: Alcon Japan; Otsuka Pharmaceuticals. Sobha Sivaprasad (Editor) has disclosed the following relevant financial relationships: Served as an advisor or consultant for: Allergan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…However, GT has several disadvantages including: extended visual rehabilitation, post-operative visual disturbance, restrictions on flying and daily activity and increased cataract formation. 1 As cataract formation is linked to the longevity of gas exposure, 1 5 air tamponade (AT) may offer reduced cataract formation, quicker rehabilitation and early detection of primary failure prior to proliferative vitreoretinopathy (PVR) formation. Using filtered air as AT following fluid-air-exchange (FAX), minimises potential operational error in GT-related concentration calculations.…”
Section: Introductionmentioning
confidence: 99%
“…However, GT has several disadvantages including: extended visual rehabilitation, post-operative visual disturbance, restrictions on flying and daily activity and increased cataract formation. 1 As cataract formation is linked to the longevity of gas exposure, 1 5 air tamponade (AT) may offer reduced cataract formation, quicker rehabilitation and early detection of primary failure prior to proliferative vitreoretinopathy (PVR) formation. Using filtered air as AT following fluid-air-exchange (FAX), minimises potential operational error in GT-related concentration calculations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bell's phenomenon might result in the exposure of breaks to intravitreal fluid and not to gas, especially when the eyes are shut 17 . Tetsumoto et al reported that the gas may act better on the peripheral retina in the supine position than in the prone position 18 . However, standard ophthalmic examinations, such as slit lamp examination, anterior segment optical coherence tomography or ultrasound biomicroscopy, do not reveal whether the tamponade gas closes the breaks when patients are in prone position or when the eyes are shut.…”
mentioning
confidence: 99%
“…Recent series have reported high success rates with air tamponade alone in RRD with inferior breaks, suggesting that tamponade in vitrectomy may not act purely by break closure, but also by a reduction in intraocular fluid currents. [49][50][51] PPV: visual outcomes Typically, visual recovery is closely linked with macular status pre-operatively, but macula-sparing cases can have worse vison postoperatively from macular involvement by displaced SRF intraoperatively, as well as some degree of epiretinal membrane (ERM) formation (35%) and CMO (15%) which can also effect visual recovery and require revision surgery for ERM in up to 15% of cases. 52 The Pneumatic Retinopexy versus Vitrectomy for the Management of Primary RRD Outcomes Randomized Trial (PIVOT) compared outcomes following PnR and PPV for primary RRD, and reported that BCVA had improved by 3 and 61 Early Treatment Diabetic Retinopathy Study (ETDRS) letters at 1 year following PPV for macula-on and macula-off RRD, respectively.…”
Section: Sb: Visual Outcomesmentioning
confidence: 99%